Analytic model for network resource management between ISPs and users. Issue 2 (1st March 2017) - Lolaee, Hossein; Akhaee, Mohammad Ali
Abstract : Fixed communication provider is a consortium of internet service providers (ISPs) in which users can switch easily and freely between their ISPs. To increase the QoS of the ISPs, the authors propose a two‐class service model. ISPs divide their available bandwidth into two parts to provide their end users with optimal services. One dedicated to primary users, and the other for secondary users. Primary users are those who pay more and thus, expect dedicated bandwidth that is always available. Secondary services are provided by ISPs for the other users who cannot afford the dedicated bandwidth. In this study, by defining the utility functions for both user types, the authors aim at dividing the ISP bandwidth between these two services such that the utility function of the users is maximised. Since the primary users do not always use the maximum bandwidth, an algorithm is proposed for ISPs to estimate the primary users' required bandwidth in each time segment based on the previous segments. Based on this estimate, the expected bandwidth is dedicated to the primary users, and the remaining bandwidth is devoted to the secondary users to improve the quality of service. On the other hand, an ISP is penalised if it fails to provide the primary users with the required bandwidth mentioned in their contract. Therefore, there exists a trade‐off between the conservative estimation of the primary users' rate, the QoS of the secondary users and the achieved utility of the ISPs.